The ECG Manual An Evidence-Based Approach - Gertsch, Marc (Springer London : Imprint: Springer, 2009)
The field of electrocardiogram (ECG)interpretation has developed extensively over the past century, and it is still a hugely influential diagnostic test that is critical for further diagnostic procedures, especially therapeutic interventions. However, not every physician and student of medicine is aware of the important theoretic basics of electrocardiology, from the important difference between the heart muscle fiber and the conduction fiber (explaining the capacity of acting as impulse generator) to the left ventricular vectors also in their simplified form and to the different grades of ischemia. Moreover the calculation of the frontal QRS-Axis (AQRSF) is provided. The author thus provides the reader with a solid grounding in the basics of electrocardiography in this highly practical and structured reference work. Appropriate for all students of medicine, Fellows in internal medicine, cardiology, and any discipline requiring an in-depth knowledge of the functioning of the heart, this book represents a lifetime's involvement with invasive and non-invasive cardiology by one of Switzerland's leading cardiologists. Numerous ECGs and drawings illustrate the text. Ease of reference is facilitated by the concentration on practical information that does not overwhelm the reader with exhaustive detail.